Direct oral anticoagulants for cancer‐associated venous thromboembolisms: a systematic review and network meta‐analysis. Issue 2 (20th February 2022) - Samaranayake, Chinthaka B.; Anderson, James; McCabe, Colm; Zahir, Syeda Farah; W. Upham, John; Keir, Gregory
Abstract: Background: Several recent randomised controlled trials (RCT) have investigated the use of direct oral anticoagulants (DOAC) in the treatment of malignancy‐associated venous thromboembolism (VTE). Aims: This meta‐analysis combines all RCT data to determine the risks of recurrent VTE and bleeding with DOAC in patients with malignancy‐associated VTE compared with low‐molecular‐weight heparin (LMWH). Methods: The study followed PRISMA guidelines. MEDLINE, EMBASE and CENTRAL were systematically searched from inception to 1 April 2020. References of reviews and relevant conference proceedings were searched by hand. Two authors independently evaluated study eligibility, extracted data and assessed risk of bias. Direct and indirect meta‐analyses were performed. Results: In four RCT with low risk of bias (2907 patients), high certainty evidence suggested that DOAC had a 37% reduction in risk of recurrent VTE compared with LMWH (direct pooled risk ratio (RR) 0.63; 95% confidence interval (CI) 0.44–0.91; I 2 = 28%). No significant difference was observed in the risk of major bleeding with DOAC compared with LMWH (RR 1.31; 95% CI 0.83–2.07; I 2 = 22%; moderate certainty evidence), including in patients in gastrointestinal and genitourinary malignancy. An increased risk of combined major or clinically relevant non‐major bleeding was seen with DOAC (RR 1.52; 95% CI 1.09–2.12; I 2 = 51%; low certainty evidence). Apixaban had the highest probability of being ranked the most effective and least bleeding risk among the DOAC. Conclusion: DOAC are effective in treating malignancy associated VTE; however, caution is required in patients with high risk of bleeding. Apixaban had lower risk of bleeding compared to other DOAC in this population.